Jawabanmu

2014-03-27T09:02:11+07:00
F(g(x))= 3(2-2x) - 5 = 13 f(g(x))= 6-6x-5=13 1-6x=13 -6x=13+1 -6x=14 x=-14/6 smoga bener ya
ini bru diterangin sma guru au. . gni carax.(f o g) (x) = 13

f (g(x))= 13 3 (2-2x) = 13 . 6-6x-5 = 13 . -6x + 1 = 13 - 1 . -6 = 12 . x = 12/-6 . x = -2 gtu
terimakasih y @echemaniezz .... udh bntu jwb
2014-03-27T09:23:08+07:00
f(x) = 3x - 5 , g(x) = 2 - 2x
fog (x) = 13
3(2 - 2x) - 5 = 13
    6 - 6x - 5 =13
         1 - 6x = 13
            - 6x = 13 - 1
            - 6x = 12
                x = - 2


semoga membantu :)